The Effect Of Liquidity, Activity And Leverage On Company Value With Profitability As Mediation Variables - Nekky Rahmiyati; Ian Natus Sholikha (Neo Journal of economy and social humanities, 2022)
This study aims to determine and analyze the effect of liquidity, activity and leverage on firm value with profitability as a mediating variable in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sample used in this study was 10 companies with purposive sampling technique to obtain 30 data. The method used is quantitative, and then data collected is analyzed using the SmartPLS 3.0 software. The result show that the liquidity, activity, and leverage have no significant effect on profitability. At the same time, the liquidity and profitability have no significant effect on firm value. At the same time, activity and leverage significantly effect on firm value. At the same time, liquidity, activity, and leverage have no significant effect on firm value with profitability as a mediating variable